Development of Banana-Based Processed Products (Banana Cake) to Create Added Value for the Banana Grower Community Enterprise, Ban Nong Yang, Hua Kwang Subdistrict, Kosumphisai District, Maha Sarakham Province - Asasri, kunteera (Journal for Developing the Social and Community, 2025)
Background and Aims: In accordance with the Sustainable Development Goals for elevating grassroots economy and driving communities toward stability, prosperity, and sustainability, the government has emphasized the development of local community economic systems to achieve self-reliance. The development of processed banana products into banana cake will enhance the potential utilization of local resources, solve market oversupply problems, generate additional income, and expand customer base to create added value for bananas. Therefore, the objectives of this research are to study product development in terms of taste, design, branding, and packaging, as well as the impact on value creation in various management aspects of the community enterprise group. Methodology: This study employs a quantitative research approach, collecting data from 50 members of the Banana Grower Community Enterprise, Ban Nong Yang, Hua Kwang Subdistrict, Kosumphisai District, Maha Sarakham Province, using questionnaires. The data were analyzed using Multiple Correlation Analysis and Multiple Regression Analysis. Results: The multiple correlation analysis and predictive equation development revealed that the overall development of processed banana cake products has a positive relationship and impact on value creation for community enterprise groups. This can be used to construct a predictive equation for overall value creation for community enterprise groups (CAV) with an adjusted coefficient of determination (AdjR²) of 0.524, as follows: CAV = -4.693 + 2.072(DBP) Conclusion: The development of banana cake products creates a clearly positive impact on community enterprise groups, with the ability to predict value creation up to 52.4% through the equation CAV = -4.693 + 2.072(DBP). The development of packaging and branding, which received high acceptance levels, helps elevate product standards and create market credibility. Processing bananas into cake increases value from the original produce, reduces post-harvest losses, and generates additional income for farmers. Meanwhile, member participation in the product development process helps strengthen community organization, develop business management skills, and create sustainable marketing networks for the community enterprise group.